2022
DOI: 10.3390/cancers14194578
|View full text |Cite
|
Sign up to set email alerts
|

The Immune Contexture of Liposarcoma and Its Clinical Implications

Abstract: Liposarcomas (LPS) are the most frequent malignancies in the soft tissue sarcoma family and consist of five distinctive histological subtypes, termed well-differentiated LPS, dedifferentiated LPS (DDLPS), myxoid LPS (MLPS), pleomorphic LPS, and myxoid pleomorphic LPS. They display variations in genetic alterations, clinical behavior, and prognostic course. While accumulating evidence implicates a crucial role of the tumor immune contexture in shaping the response to anticancer treatments, the immunological lan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 162 publications
0
8
0
Order By: Relevance
“…In our patient cohort consisting of various STS, half of the samples had more than 2/3 of the total tumor area positive on CD47 staining. To offer a more profound insight, we have divided LPS according to their histological subtypes, because we are aware of their considerable differences (Resag et al 2022 ). Interestingly, only one WDLPS out of all 22 LPS specimens, did not express CD47.…”
Section: Discussionmentioning
confidence: 99%
“…In our patient cohort consisting of various STS, half of the samples had more than 2/3 of the total tumor area positive on CD47 staining. To offer a more profound insight, we have divided LPS according to their histological subtypes, because we are aware of their considerable differences (Resag et al 2022 ). Interestingly, only one WDLPS out of all 22 LPS specimens, did not express CD47.…”
Section: Discussionmentioning
confidence: 99%
“…Also RHT, a frequently used treatment for extremity STS, was reported to show immunogenic effects ( 37 ). Boosting the pre-existing immune TME is of particular interest for STS, as they generally exhibit a low to moderate T cell infiltration compared to other tumor entities with major differences between STS subtypes ( 38 42 ). However, in our study, CD3 + and CD8 + T cell densities showed a trend to decrease following neoadjuvant therapy.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, five distinct subtypes of liposarcoma display major variations in the composition of the TME [29]. While dedifferentiated liposarcoma became the predominant liposarcoma subtype evaluated in clinical trials with immune checkpoint inhibitors due to its relatively high infiltration with T cells, myxoid liposarcoma has become a prime target for CAR T-cell therapy [41]. Since a large portion of dedifferentiated liposarcomas derive from well-differentiated liposarcomas, we aimed to evaluate the immunotherapy responses in this particular liposarcoma subtype [41].…”
Section: Discussionmentioning
confidence: 99%
“…While dedifferentiated liposarcoma became the predominant liposarcoma subtype evaluated in clinical trials with immune checkpoint inhibitors due to its relatively high infiltration with T cells, myxoid liposarcoma has become a prime target for CAR T-cell therapy [41]. Since a large portion of dedifferentiated liposarcomas derive from well-differentiated liposarcomas, we aimed to evaluate the immunotherapy responses in this particular liposarcoma subtype [41]. However, our limited cohort size hampered prediction of treatment response based on histological subtype of STS.…”
Section: Discussionmentioning
confidence: 99%